A TP53-associated gene signature for prediction of prognosis and therapeutic responses in lung squamous cell carcinoma. (1st January 2020) - Xu, Feng; Lin, Haoyu; He, Pei; He, Lulu; Chen, Jiexin; Lin, Ling; Chen, Yongsong
ABSTRACT: The tumor-suppressor gene tumor protein p53 ( TP53 ) is one of the most commonly mutated genes in human lung cancer, and TP53 mutations are associated with a worsened prognosis and causes resistance to cancer therapy. RNA sequencing and TP53 mutation data were downloaded to determine specific TP53 -associated signature based on differentially expressed genes between patients with lung squamous cell carcinoma (LUSC) with wild type ( TP53  WT ) and mutated ( TP53 MUT ) TP53 . We investigated the predictive value of this signature on the immune microenvironment, tumor mutational burden (TMB), and likelihood of response to immunotherapy and chemotherapy. In total, 1, 556 differentially expressed genes were identified based on TP53 mutation status. Three genes (KLK6, MUC22 and CSN1S1) identified by univariate and multivariate Cox regression analyses, comprised the prognostic signature which was an independent and specific prognostic marker of overall survival in patients with LUSC. A nomogram was also established to validate this signature for clinical use. Moreover, the high-risk group was characterized by increased infiltration of monocytes and macrophages M1, and decreased T cells CD8 and T cells follicular helper. High-risk group exhibited a higher TMB, and was much more sensitive to immunotherapy and chemotherapy. KLK6 and CSN1S1 expression and the prognostic prediction values were further validated in clinical samples. The derived TP53 -associated signature is a specific and independent prognostic biomarker for LUSC patients, and could provide potential prognostic biomarker or therapeutic targets for the development of novel immunotherapies and chemotherapies.